Mechanical and dielectric properties of CaCu3Ti4O12 and La doped CaCu3Ti4O12 poly(vinylidene fluoride) composites - Srivastava A.; Maiti P.; Kumar D.; Parkash O. (My University, 2025)
Giant dielectric constant CCTO and La doped CCTO (LaCCTO) reinforced PVDF composites were prepared through melt extrusion process. The structure and morphology of the composites were characterized using X-ray diffraction, thermal analysis, contact angle measurement and scanning electron microscope. Tensile tests were performed to measure Young's modulus which increases significantly in composites in presence of ceramic filler. Dielectric measurements were carried out in the frequency range 10-2-106Hz using four probe Novocontrol set up (ZG4) in a wide range of temperature (room temp to 120°C) to observe the relaxation behaviour as a function of temperature. On adding CCTO and LaCCTO there is substantial increase in the dielectric constant of the matrix PVDF. Dielectric loss increases slightly with increasing temperature and decreases with increasing frequency. Dielectric loss in the composites increases in presence of CCTO while it decreases in La doped CCTO reinforced composite. Temperature dependent dielectric relaxation has been studied using H-N function. The relaxation peak has shifted toward higher frequency in composites suggesting lowering of relaxation time. The relaxation time (τ) considerably decreases in composites as compared to pure PVDF indicating greater grain movement of smaller crystallite size of ceramic in composite. © 2014 Elsevier Ltd.